Vocational Education and the New Federalism. Special Report - American Vocational Association, Arlington, VA.; American Vocational Association, Arlington, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The new federalism plan and the fiscal year 1983 budget presented to Congress by the Reagan administration call for changes that would, within the next few years, eliminate all federal involvement in vocational education. The proposed plan for budget cuts, block grants, and eventual phaseout of all federal involvement in all federal government has no obligation to reduce unemployment and shortages of skilled workers or to enable special populations to succeed in vocational education. On the contrary, the basis for federal involvement in vocational education remains the same today as it was when Congress initially established the concept of federal support for vocational education. Cuts in federal funding for vocational education will hurt individuals, employers, and schools. Despite Administration claims, it is highly unlikely that state support can now be found to make up for the proposed real dollar reductions. If for no other reason, the federal government should continue to support vocational education because it is a program that more than repays the government for its investment. Finally, removal of the federal government from involvement in vocational education may result in the collapse of education-for-work capability. (MN)
Availability: The American Vocational Association, Inc., 2020 North Fourteenth St., Arlington, VA 22201 ($3.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education Work Relationship; Educational Finance; Educational Needs; Federal Aid; Financial Support; Government Role; Government School Relationship; Grants; Investment; Position Papers; Public Policy; School Districts; State Action; State Federal Aid; State Programs; Vocational Education; New Federalism; Reagan Administration; Opinion Papers